Tumor necrosis factor-alpha contributes to obesity-related hyperleptinemia by regulating leptin release from adipocytes. - Kirchgessner, T G (1997)
Cytokines, in particular tumor necrosis factor-alpha (TNF-alpha), have significant effects on energy metabolism and appetite although their mechanisms of action are largely unknown. Here, we examined whether TNF-alpha modulates the production of leptin, the recently identified fat-specific energy balance hormone, in cultured adipocytes and in mice. TNF-alpha treatment of 3T3-L1 adipocytes resulted in rapid stimulation of leptin accumulation in the media, with a maximum effect at 6 h. This stimulation was insensitive to cycloheximide, a protein synthesis inhibitor, but was completely inhibited by the secretion inhibitor brefeldin A, indicating a posttranslational effect. Treatment of mice with TNF-alpha also caused a similar increase in plasma leptin levels. Finally, in obese TNF-alpha-deficient mice, circulating leptin levels were significantly lower, whereas adipose tissue leptin was higher compared with obese wild-type animals. These data provide evidence that TNF-alpha can act directly on adipocytes to regulate the release of a preformed pool of leptin. Furthermore, they suggest that the elevated adipose tissue expression of TNF-alpha that occurs in obesity may contribute to obesity-related hyperleptinemia.